Understanding the relationship between crime victimisation and mental health: a longitudinal analysis of population data - Karen Freeman
Being a victim of violent crime has a damaging effect on mental health, particularly for women, according to this report. The needs and experiences of victims of crime have become increasingly recognised as an important aspect of criminal justice and public policy. In Australia, victim support services grew from community-based organisations and lobby groups. With the passage of time, these services have become increasingly formalised, with the State progressively assuming a greater role in advocacy and service provision for victims of crime. While we know that many Australians will experience an incident of crime in their lifetime, the effect of this victimisation on health has not been sufficiently explored. This is unfortunate given the demand for victim support services; close to 6,000 applications for counselling assistance in 2011/12 were received by the Victims Compensation Tribunal, New South Wales. As such, it is timely to examine more closely the nature of the relationship between becoming a victim of crime and an individual’s subsequent mental health.   &nbsp